Medical professionalism in late capitalism: perceptions of the medical students at Universidad de Chile - Pesse-Sorensen, Karen (2017)
Introduction: Medical professionalism is facing a crisis due to the transition from liberal practice to becoming employees of corporations that manage health related issues with criteria corresponding to the prevailing socioeconomic model which also influences medical concepts and practices. Objectives: To describe how medical students perceive their professionalism; to identify influencing contextual factors and to portray its implications in student´s lives and professional performance. Design: Qualitative research framed in a study regarding the contribution of the rural internship to the medical undergraduate program. Participants: Last year students of medical school. Setting. Faculty of Medicine, Universidad de Chile. Interventions. Fifteen semi-structured interviews were performed to students in their last year at medical school. Narrative analysis followed by interpretation of its meaning was applied to the resulting information. Main outcome measures: Perception of professionalism. Results: Strong tension exists between professionalism´s core principles and values and institutional and contextual factors shaping current medical practice. Interviewees take their duty to respond to patient's demands and needs with high sense of responsibility, developing individual strategies to overcome system´s limitations and cope with arising frustrations. Conclusions: Evidence on how medical students perceive and try to cope with these contradictions poses the need for a profound transformation of medical education. Focusing on the collective is proposed as conceptual base as well as key mechanism of this change.